One-pot sol-gel process and simultaneous formation silica particles cross-linked network (SPCN) - Nguyen Nhat Nam (Communications in Science and Technology)
In this work, a simple sol-gel process method was studied for “one-pot” fabrication of silica particle cross-linked networks (SPCN). It is the first time that the co-precursors of tetraethoxysilane (TEOS) and ?-glycidoxypropyltrimethoxysilane (GPTMS) and capping agent of cetyltrimethylammonium bromide (CTAB) are formulated to achieve the complete co-polymerization of the reaction solution. The reaction solution proposed involved TEOS and GPTMS (5:1 w/w) for feasibility preparation of SPCN. The copolymerization temperature was set at 40? for 24h of aging time. The results indicated that, by means of cetyltrimethylammonium bromide as a capping agent, SPCN exhibited a well-defined three-dimensional (3D) porous network. The prepared SPCN was used for the synthesis of silica monolithic columns to show interstices distributed across the whole SPCN as well as monolithic columns. The BET surface area of the SPCN column was obtained at approximately 156 m2/g and an average pore width smaller than 26 nm.